2019
DOI: 10.3892/mmr.2019.9986
|View full text |Cite|
|
Sign up to set email alerts
|

High glucose promotes hepatic fibrosis via miR‑32/MTA3‑mediated epithelial‑to‑mesenchymal transition

Abstract: Hepatic fibrosis is characterized by the aberrant production and deposition of extracellular matrix (ECM) proteins. Growing evidence indicates that the epithelial-mesenchymal transition serves a crucial role in the progression of liver fibrogenesis. Although a subset of microRNAs (miRNAs or miRs) has recently been identified as essential regulators of the EMT gene expression, studies of the EMT in hyperglycemic-induced liver fibrosis are limited. In the current study, it was observed that high glucose-treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…As the main components of ECM, Col‐I and Col‐III are enhanced in fibrotic liver. The protein and mRNA expression of Col‐I increase in hyperglycemia‐induced hepatic fibrosis in rats . Carbon tetrachloride (CCl 4 ) can accumulate a significant amount of Col‐III in mouse liver .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the main components of ECM, Col‐I and Col‐III are enhanced in fibrotic liver. The protein and mRNA expression of Col‐I increase in hyperglycemia‐induced hepatic fibrosis in rats . Carbon tetrachloride (CCl 4 ) can accumulate a significant amount of Col‐III in mouse liver .…”
Section: Discussionmentioning
confidence: 99%
“…16 The protein and mRNA expression of Col-I increase in hyperglycemia-induced hepatic fibrosis in rats. 42 Carbon tetrachloride (CCl 4 ) can accumulate a significant amount of Col-III in mouse liver. 43 Increasing expressions of Col-I and Col-III are related to hepatic fibrosis 44 and bile duct ligation.…”
Section: Nano Nio Induced Hepatic Fibrosis In Ratsmentioning
confidence: 99%
“…Cell viability was detected with Cell Counting Kit-8 (CCK-8; Dojindo, Kumamoto, Japan) as previously described by our laboratory 24 . Briefly, neonatal cardiomyocytes (60% confluence) were cultured in 96-well plates followed by constructive transfection or hypoxia treatment.…”
Section: Methodsmentioning
confidence: 99%
“…23,24 Li et al found that the pathological silencing of miR-32 could improve hepatic fibrosis. 25 However, there was no direct evidence to support the role of miR-32 in DN fibrosis. In this study, we observe that miR-32 overexpression potentiates EMT process in HG-incubated HK-2 cells, exhibited by the upregulation of α-SMA and vimentin expressions as well as the downregulation of E-cadherin expression.…”
Section: Discussionmentioning
confidence: 99%
“…Increased expression of miR-32 was found in type Ⅱ diabetes patients with obesity and streptozotocin (STZ)-induced diabetic rats. 9,10 A previous study revealed that miR-32 level was obviously enhanced in kidney tissue during chronic allograft dysfunction with interstitial fibrosis and tubular atrophy, 11 implying that miR-32 may be associated with renal fibrosis. However, the role and underlying mechanisms of miR-32 are elusive in DN.…”
Section: Introductionmentioning
confidence: 99%